The Effect of Health Education About Personal Hygiene in Adolescents on the Prevention of Scabies Disease in Boarding School in Sungai Terap - Ramadhini, Agvira Destri; Nurlinawati, Nurlinawati; Mulyani, Sri (Riset Informasi Kesehatan, 2023)
Background: Scabies or scabies is an infectious skin disease caused by investment and sensitization of the parasite Sarcoptes Scabiei of the Hominis variety. The World Health Organization (WHO) states that scabies is a very neglected skin disease. It is estimated that 200 million people worldwide suffer from scabies at any one time. The Muara Kumpeh Inpatient UPTD Health Center, located in Muaro Jambi Regency, has the highest incidence of scabies, recorded throughout 2022 there were 112 cases. Based on these data, scabies is experienced by many students or students, one of whom is a student at the Jauharul Falah Islamic Boarding School. This study aims to determine the effect of health education about personal hygiene in adolescents on the prevention of scabies at the Jauharul Falah Islamic Boarding School, Sungai Terap. Methods: This study used a quantitative method with pre-experimental designs with the "One Group Pre-Test-Post-Test Design". This research was conducted at the Jauharul Falah Islamic Boarding School in Sungai Terap, Muaro Kumpeh. from September 2022-May 2023. The time for data collection was carried out in June 2023. The population in this study were all class VII students of the Jauharul Falah Islamic Boarding School Sungai Terap, totaling 113 people. The sample is 30 respondents. The sampling technique is simple random sampling. The statistical test used is the paired sample t-test. Results: The results of the study found that the average prevention of scabies in adolescents before being given health education about personal hygiene was 45.90 (out of a total score of 88). After being given health education about personal hygiene was 80.87. There is a significant effect of health education about personal hygiene in adolescents on scabies prevention behavior at the Jauharul Falah Islamic Boarding School Sungai Terap (p-value: 0.000 <0.05). Conclusion: The average difference in the prevention of scabies in adolescents before and after being given health education about personal hygiene is 34.96. It is hoped that the UPTD Inpatient Health Center at Muara Kumpeh Health Center can work together with the Jauharul Falah Islamic Boarding School Sungai Terap to educate teenagers (Santriwan and Santriwati) to always pay attention to personal hygiene, not to borrow clothes from friends so that the incidence of scabies at the Jauharul Falah Islamic Boarding School Sungai Terap can minimized. Keywords: Health Education, Personal Hygiene, Adolescents, Scabies Prevention